Research on energy-efficient physical-layer secure transmission mechanism in decode-and-forward cooperative networks - Dong WANG; Yong-cheng LI; Bo BAI; Man-xi WANG (Tongxin xuebao)
The maximization problem of secure energy efficiency (EE) in decode-and-forward relay networks was investigated considering the power and energy constraints in physical-layer secure transmission.An iterative algorithm for power allocation was proposed based on fractional programming and DC (difference of convex functions) programming.This algorithm jointly allocated power for source and relay nodes to achieve energy-efficient secure transmission,subject to the peak power constraint of each node and the minimum secrecy rate requirement of the system.Simulation results demonstrate that the propose algorithm can improve the secure EE significantly compared with the conventional secrecy rate maximization strategy.